A tailored space syntax approach to the preservation and development of a cultural park. Issue 1 (10th January 2019) - Ma, Ke; Yi, Ting; Chen, Feihu
Abstract : Chinese civilisation provides fertile ground for the development of cultural heritage tourism products. Against the backdrop of an increased focus on the national preservation of traditional Chinese culture and the rapid development of tourism, this study used a tailored space syntax approach to investigate the space design of China's Meishan culture park, which displays traditional cultural elements of Meishan regions. Originating from Meishan settlements, the overall space of China's Meishan culture park consists mainly of development along local mountains, including main roads and branches. The overall layout of the park combines centralisation and decentralisation. In space syntax analyses, the global space as well as areas, nodes and buildings were analysed, and their characteristics and functions in attracting and gathering tourists as well as preserving traditional culture were discussed. In the process of gradual development, the ecological natural environment and flexible space layout have been maintained. The adaptive space design developed could provide a reference for the optimal development of other cultural parks.